Taxation and Accounting Data Management: An Empirical Study in Cameroon (Global Journal of Management and Business Research, 2022)
This paper analyses the relationship between taxation and accounting data management in the Cameroonian context, based on a sample of 1474 firms in the period 2014-2017. This link is estimated using a simultaneous equation model which allows us to highlight the reciprocal influence between the two variables. The results show that fiscal pressure has a positive two-way effect on discretionary accruals, although this relationship is negative in large companies. The findings also show a non-linear relationship between discretionary accruals and effective tax rate. It is concave in small and medium-size enterprises. That is, at low levels of effective tax rate, the relationship is positive; it becomes negative at higher levels. Conversely, it assumes a U-shape form in large companies; meaning that, at low levels of effective tax rate the relationship is negative, becoming positive at higher levels.
Keywords: taxation; accounting data management; discretionary accruals; effective tax rate